FANTASI MINIATUR DENGAN TEKNIK LOW HIGH KEY DAN LOW KEY DALAM FOTOGRAFI SENI - Safira Aulia; Rabernir Rabernir (Jurnal Ilmiah Publipreneur, 2014)
This research explores the creation of photographic works of art with objects small objects as miniature man made in a story. Activities that are reflected in this miniature photos represent the author's personal experiences. Techniques of low key and high key are used as the supporter of the atmosphere in this miniature fantasy photos. Low key gives the feel of a dramatic, mysterious, sad, tense, whereas high key gives the feel of a cheerful, uplifting, and witty. The method used is experimental by sketching pictures, continued by making accessories and properties, adjust the lighting and composition the miniature that will be in the photo. In this final project work that generated tells different themes with theme support lighting.